2001
DOI: 10.1109/66.964323
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of novel cleaning solutions with various chelating agents for post-CMP cleaning on poly-Si film

Abstract: Abstract-In this study, various cleaning solutions containing chelating agents with carboxyl acid group ( COOH), such as ethylenediaminetetraacetic acid, citric acid and oxalic acid, were developed for post-poly-Si CMP cleaning. The chelating agent and tetramethylammonium hydroxide (TMAH) were simultaneously added into 2% ammonium hydroxide alkaline solution to promote the removal efficiency on particles and metallic impurities. The effectiveness of various cleaning recipes and their interaction mechanism with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Pan [1] studied some post-poly-Si CMP cleaning solutions containing chelating agents with carboxyl acid group (-COOH), such as ethylene diamine tetra acetic acid, citric acid and oxalic acid which are all solid agents. Patri [3] emphasized molecular structure of some chelating agents such as different functional groups, the length of the carbon chain and the relative positions of different functional groups.…”
Section: Requirements For Chelating Agents In Silicon Wafer Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Pan [1] studied some post-poly-Si CMP cleaning solutions containing chelating agents with carboxyl acid group (-COOH), such as ethylene diamine tetra acetic acid, citric acid and oxalic acid which are all solid agents. Patri [3] emphasized molecular structure of some chelating agents such as different functional groups, the length of the carbon chain and the relative positions of different functional groups.…”
Section: Requirements For Chelating Agents In Silicon Wafer Processmentioning
confidence: 99%
“…The slurry used in polishing procedure is a crucial factor influencing metal pollution level because the metal ions in polishing slurry tend to adhere on Si surface. Especially the fast diffusing metallic impurities such as copper, iron and chromium, even the least bit of contamination, will induce many crystal defects and may extend the current of device, evoke p-n junction strike out and so on [1].…”
Section: Introductionmentioning
confidence: 99%
“…These ligands coordinate with metal ions through their electron-donating atoms, resulting in the formation of highly stable cyclic chelates that resist dissociation [ 4 ]. In the realm of integrated circuits and microelectronics, chelating agents play a critical role and find widespread applications in various processes, including substrate polishing, cleaning, and even thin film layer etching [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Experiments conducted by Xie et al showed that the slurry containing 20 mmol of ammonium citrate caused a 71.6% increase in the MRR compared to the control group. Compared to the above additives, new additives with amine groups have also become popular additives for silicon wafer CMP, due to the following advantages: (1) they can achieve a higher MRR (>500 nm/min) [19,20], (2) they do not introduce contamination with metal ions such as Na + , K + , etc., and (3) they can be used as chelating agents to remove metal ions [21,22]. Polyamines are a representative class of amine additives that can achieve large MRR improvements.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional MD simulations based on classical force fields can simulate the dynamic evolution of large systems with thousands or even tens of thousands of atoms, but they have the disadvantage of not being able to describe the chemical reactions. Compared to the above additives, new additives with amine groups have also become popular additives for silicon wafer CMP, due to the following advantages: (1) they can achieve a higher MRR (>500 nm/min) [19,20], (2) they do not introduce contamination with metal ions such as Na + , K + , etc., and (3) they can be used as chelating agents to remove metal ions [21,22]. Polyamines are a representative class of amine additives that can achieve large MRR improvements.…”
Section: Introductionmentioning
confidence: 99%